Synthesis, Characterization and Antibacterial Study of Selected Metal Complexes Derived from Modified of PVA - Ruwaidah S. Saeed (Journal of Global Pharma Technology, 2019)
A new ligands(modifier polymers) L1, L2, L3 , L4 and L5 were prepared according to method [8] by reaction of polyvinyl alcohol(PVA) withi(acid chloride)[1]a or [2,3]a,b in dimethyl formamide. The Ligands were characterized by (FT-IR), (UV- Vis) and (1H-NMR) spectra some of them. Synthesis some transition metals complexes of these ligands and described via (FT-IR, UV-Vis) spectra, [Thermo gravimetric analysis (TGA), Differential Scanning Calorimetry (DSC)], (SEM) and antibacterial activity was screened thought two types of bacteria. The octahedral geometrical was suggested for Co+2, square Planer geometrical was suggested for Ni+2and tetrahedral geometrical was suggested for Cd+2Keywords: PVA; Metal complexes; Antibacterial.